Glove versus controller: the effect of VR gloves and controllers on presence, embodiment, and cognitive absorption - Palombo, Raphael; Weber, Sebastian; Wyszynski, Marc; Niehaves, Björn (Frontiers in Virtual Reality, 2024)
Introduction: Using our own hands allows humans to interact with the real world, as we learn from an early age. Virtual reality (VR) gloves allow a similar interaction in VR by transferring hand movements through natural mapping. Research outside the VR domain has already shown that this process creates a high level of presence and perceived naturalness. Research in the VR context, on the other hand, is still in an early stage and lacks explorative qualitative research following a human-centered approach and including the direct perceptions of users on mapped controls in system design. Against that background, this research investigates natural mapping in the VR context qualitatively. The study examines how participants experience VR input devices with different degrees of natural mapping (VR gloves, a Valve index controller, and an HTC Vive controller) on perceived naturalness, spatial presence, embodiment, and cognitive absorption. Methods: A focus group (N = 20 aged 22–36) did the VR experience with the devices and was asked about their experience in semi-structured interviews. Questions focused on perceived naturalness, spatial presence, cognitive absorption, and embodiment with the three devices. Data were analyzed using qualitative content analysis. Results: Feedback on spatial presence was widely positive for the VR glove due to the highly natural perceived movement capabilities. Mapping with the partly mapped index controller was also seen as natural and immersing if the movement matched the operated actions in the system. Participants mainly perceived the highest degree of cognitive absorption and embodiment while doing the task with the VR glove. Discussion: The findings indicate that the natural mapping capabilities of VR input devices strongly influence spatial presence. The VR glove stands out while being able to induce a feeling of embodiment in most cases. Furthermore, participants reported a connection between natural mapping and perceived cognitive absorption in the task.